Curative effect of neutral macroporous resin hemoperfusion on treating hemodialysis patients with refractory uremic pruritus. Issue 12 (March 2017) - Li, Wen-Hong; Yin, Yu-Min; Chen, Hao; Wang, Xiao-Dan; Yun, He; Li, Hui; Luo, Jie; Wang, Jin-Wen
Abstract : Abstract: This study aims to investigate the efficacy and safety of neutral macroporous resin hemoperfusion in treating maintenance hemodialysis (MHD) patients with refractory uremic pruritus (RUP). Ninety patients were enrolled and were randomly divided into 3 groups: control group, experiment 1 group, and experiment 2 group. Clinical symptom scores of skin itching were recorded before and at 4 and 8 weeks after the treatment. In addition, serum parathyroid hormone (PTH), calcium (Ca 2+ ), phosphorus (P 3+ ), and C-reactive protein (CRP) were detected; and the calcium–phosphorus product ([Ca] × [P]) was calculated to compare the curative effect. VSA score, modified Duo pruritus score, and CRP: these indices decreased to some extent at 4 and 8 weeks after treatment in the 2 experiment groups, compared with pretreatment ( P < 0.05); and differences among these 3 groups were statistically significant ( P < 0.05). PTH, P 3+, and [Ca] × [P]: these indices decreased to some extent at 4 and 8 weeks after treatment in the 2 experiment groups, compared with pretreatment ( P < 0.05); and differences between the control and experiment 1 groups, as well as between the control and experiment 2 groups, were statistically significant ( P < 0.05). However, the difference between the experiment 1 and experiment 2 groups were not statistically significant ( P < 0.05). The effects of HA330 and HA130 resin hemoperfusion apparatus on secondary hyperparathyroidism and the disorder of calcium and phosphorus metabolism are similar. The mechanism may be related to its strong adsorption effect, and its capacity to widely remove inflammatory mediators, immune mediators, and endotoxins.